BRAF V600E mutational status in pediatric thyroid cancer. Issue 7 (27th March 2014) - Henke, Lauren E.; Perkins, Stephanie M.; Pfeifer, John D.; Ma, Changquing; Chen, Yumei; DeWees, Todd; Grigsby, Perry W.
Abstract Background Clinical outcome of papillary thyroid carcinoma (PTC) in children differs significantly from that of adults. There is no clear explanation of this difference although previous studies have demonstrated a lower prevalence of the BRAFV600E mutation in PTC of children. However, data are limited due to the rarity of this diagnosis. BRAFV600E mutation prevalence and its relationship with outcome in pediatric PTC remain unclear. Procedure BRAF V600E mutational status was determined in 27 PTC patients less than 22 years of age using restriction fragment length polymorphism (RFLP) analysis. The relationship between BRAFV600E mutation status, patient and tumor characteristics as well as progression‐free survival (PFS) were analyzed. Results BRAF V600E was present in 63% of patients and occurred more often in male patients versus females (P = 0.033). Presence of the mutation did not correlate with any difference in extent of disease at diagnosis, tumor size, capsular invasion, vascular invasion, soft tissue invasion, or margin status. At 10 years, PFS for BRAFV600E positive versus negative patients was 55.5% versus 70.0%, respectively (P = 0.48). Overall survival was 100% and median follow‐up was 13.9 years. Conclusions This study of pediatric PTC demonstrates that BRAFV600E mutations occur in children at a rate comparable to adults. We found a correlation of BRAFV600E with the male gender, but no evidence that the mutation correlates with more extensive or aggressive disease. This analysis suggests that differences in disease course of PTC in children versus adults are not strongly dependent upon the presence of the BRAFV600E mutation. Pediatr Blood Cancer 2014;61:1168–1172. © 2014 Wiley Periodicals, Inc.